2023
DOI: 10.1097/gox.0000000000005095
|View full text |Cite
|
Sign up to set email alerts
|

“Spin” in Observational Studies in Deep Inferior Epigastric Perforator Flap Breast Reconstruction: A Systematic Review

Abstract: Breast reconstruction after mastectomy in breast cancer patients is known to provide significant improvements in psychological well-being. 1 Among various techniques available, the deep inferior epigastric perforator (DIEP) flap is considered to be the gold standard for autologous breast reconstruction. 2 Despite the clinical importance and high regard of the DIEP flap technique, most research studies in leading plastic surgery journals are nonrandomized and observational in nature. 3 Nonrandomized observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…Both studies identified a similar prevalence of spin strategies in their included studies (Lazarus et al 84%, Kim et al 85.7%). In terms of level of spin, Lazarus et al [7] found 67% of their included studies used moderate to high levels in their conclusions, while Kim et al [10] found 86.9%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Both studies identified a similar prevalence of spin strategies in their included studies (Lazarus et al 84%, Kim et al 85.7%). In terms of level of spin, Lazarus et al [7] found 67% of their included studies used moderate to high levels in their conclusions, while Kim et al [10] found 86.9%.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 235 included studies, 81.3% contained spin, with 54.9% containing moderate or high levels of spin in their conclusions. To date, there are only two studies that have assessed spin in observational studies: the initial study by Lazarus et al [7] that defined the spin criteria for observational studies, and a recent study by Kim et al [10] assessing spin in observational studies about deep inferior epigastric perforator flap breast reconstruction. Both studies identified a similar prevalence of spin strategies in their included studies (Lazarus et al 84%, Kim et al 85.7%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations